SOSIALISASI DAN EDUKASI PENINGKATAN MOTIVASI BELAJAR MATEMATIKA SISWA DI SMKN 2 PADANG - Fitri, Yuliani; Refnywidialistuti; Teni Suriani (Ekasakti Jurnal Penelitian dan Pengabdian, 2023)
This volunteer study was conducted due to the lack of students’ motivation in learning mathematics at SMKN 2 of Padang. The study was aimed to helped students become motivated in learning mathematics. Learning motivation was provided to the students and followed by Sudoku game to sharpen their thinking ability. For the students who can do it fastest and correctly are given reward. By doing this activities, the students seem to be motivated and carious in learning the subject. The activity is relevant to the finding of some studies conducted in advance concerning with motivation in learning mathematics.